2022
DOI: 10.1038/s41419-022-04930-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel 3’tRNA-derived fragment tRF-Val promotes proliferation and inhibits apoptosis by targeting EEF1A1 in gastric cancer

Abstract: At present, it is commonly believed that tRFs and tiRNAs are formed by the specific and selective shear of tRNAs under certain pressure stimulation, rather than by random degradation of tRNA. tRFs and tiRNAs have been reported to contribute to the biological process of a variety of human cancers. However, the evidence for the mechanisms of tRFs and tiRNAs in the occurrence and development of gastric cancer (GC) is still insufficient. Here, we aimed to explore the carcinogenic roles of tRFs and tiRNAs in GC wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
(48 reference statements)
1
41
0
Order By: Relevance
“…In this study, we find that tRF-5c were the most abundant categories in pig spleen. Previous studies showed that the class of tsRNA in stomach [ 59 ], lung [ 60 ] and plasma [ 61 ] were mainly tRF-5c. However, other results were also reported tiRNAs were primarily observed in ovary [ 62 ] and thyroid [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we find that tRF-5c were the most abundant categories in pig spleen. Previous studies showed that the class of tsRNA in stomach [ 59 ], lung [ 60 ] and plasma [ 61 ] were mainly tRF-5c. However, other results were also reported tiRNAs were primarily observed in ovary [ 62 ] and thyroid [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RNAi abilities, GC-related tRF can also interact with RBPs. Recently, Cui and colleagues identified a 3’-tRF named as tRF-Val as a potential oncogene in GC and confirmed the interaction of tRF-Val with the chaperone molecule EEE1A1 [ 119 ]. They further unraveled that tRF-Val mediated the transport of EEF1A1 to the nucleus, thus improving the interaction of EEF1A1 and MDM2-p53, which resulted in p53 ubiquitination and blockade of p53 signaling pathways [ 119 ].…”
Section: Biological Roles and Clinical Values Of Trfs In Cancermentioning
confidence: 99%
“…In addition, tRNA fragments impact apoptosis. The 3′-tRNA-derived fragment, tRF-Val, inhibits apoptosis by binding to the chaperone molecule, eukaryotic translation elongation factor 1 alpha 1, directly and inhibiting the downstream p53 molecular pathway in gastric cancer [ 109 ]. Furthermore, tRF-315 derived from tRNA-Lys alleviates cisplatin-induced mitochondrial dysfunction and apoptosis in prostate cancer [ 110 ].…”
Section: Biological Functions Of Tsrnasmentioning
confidence: 99%